Comparative Study on Interdental Papillae Regeneration: Leukocyte Platelet-Rich Fibrin By-product versus Hyaluronic Acid Injections in Modified Open Gingival Embrasure Model - Sari, Rezmelia; Sukorini, Usi; Susilowati, Heni; Suryono, Suryono (European Journal of Dentistry, 2025)
Objectives This study aims to compare the regenerative effects of various by-products of human leukocyte platelet-rich fibrin (L-PRF), including L-PRF exudate, concentrated PRF (C-PRF), and a mixture of the two, with hyaluronic acid (HA) specifically for interdental papillae reconstruction.Materials and Methods The L-PRF was obtained by centrifuging 10 mL of human blood in a fixed-angle centrifuge at 2,700 rpm for 12 minutes. After centrifugation, the L-PRF layer was separated, and platelet and leukocyte counts were performed. An in vivo study was conducted using Sprague-Dawley rats subjected to a modified open gingival embrasure (OGE) model for 7 days. Once the OGE was established, 20 µL of L-PRF exudate (n = 3), C-PRF (n = 3), a combination of L-PRF exudate and C-PRF (n = 3), HA (n = 3), and phosphate-buffered saline (n = 3) were injected 2 mm from the tip of the papillae using a 30G syringe. Clinical parameters, including OGE width and spring papilla distance (SPD), were observed on days 7 and 14. On day 14, histological observations included fibroblast count, blood vessel presence, epithelial width, and collagen density, while proliferating cell nuclear antigen expression was assessed immunohistochemically.Statistical Analysis The SPD on day 7, along with all histological and immunohistochemical data, were normally distributed and analyzed by one-way analysis of variance followed by Tukey's honestly significant difference test. In contrast, the Kruskal–Wallis' test was used to analyze the OGE width and SPD on day 14, which was not normally distributed.Results The cell counts indicated that most platelets and leukocytes were in the C-PRF layer. The L-PRF membrane by-product increased fibroblast proliferation more effectively than HA (p < 0.05). Only C-PRF significantly enhanced the vascularization and epithelialization of the papillae (p < 0.05). However, the observed cellular and molecular changes increased at day 7 postinjection and did not impact collagen density or interdental papilla height.Conclusion The regenerative effect of C-PRF injection is superior to that of HA and other L-PRF by-products, as it promotes papillae regeneration by enhancing fibroblast activity, vascularization, and epithelialization. These findings show the potential impact of L-PRF by-products as a nonsurgical papillae reconstruction treatment.
Keywords: cell proliferation; gingiva; hyaluronic acid; open gingival embrasure; platelet-rich fibrin; regeneration